PROTECTIVE MECHANICAL VENTILATION IN PATIENTS WITHOUT OR WITH LUNG INJURY - Sutherasan Yuda; Vargas Maria; Rodríguez-González Raquel; Pelosi Paolo (Sanamed, 2014)
The mortality of Acute Respiratory Distress Syndrome (ARDS) is still high from 27 to 45% according to Berlin definition. Even in surgical patients without lung injury, the postoperative pulmonary complications (PPCs) are frequent. Mechanisms of ARDS, ventilator associated lung injury (VALI) and PPCs are better understood. In ARDS, protective ventilation with low tidal volume 6 ml/kg PBW and higher levels of positive end-expiratory pressure (PEEP) is widely accepted as routine practice. In no ARDS patients undergoing mechanical ventilation, protective ventilation with low tidal volume 6ml/kg PBW and low to moderate levels of PEEP has become the new challenge paradigm shift of supportive care mainly in ICU and perioperative patients. Respiratory monitoring is very helpful for optimizing mechanical ventilator setting to prevent VALI and early detect PPCs during the perioperative period. Several scores have been developed to stratify the risk of ARDS, VALI and PPCs. It’s time to apply basic physiologic knowledge of respiratory function and evidence based practice to improve ARDS and PPCs outcomes.